1966
DOI: 10.2307/2406148
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variation in Natural and Experimental Populations of Drosophila pseudoobscura and Drosophila persimilis

Abstract: Drosophila pseudoobscura and its sibling D. persimilis are two species of fruit flies which have received considerable attention from the standpoint of population genetics. Examination of the arrangements (inversions) in the third chromosome in salivary gland cells of the larval progeny of flies derived from many geographic localities throughout the distribution of these species reveals that (1) populations within a locality are largely polymorphic; (2) populations from different altitudes and latitudes differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
2
36
1
Order By: Relevance
“…Two traits in Drosophila known to be associated with fitness that are under different selection regimes are ovariole number (stabilizing selection; Wayne & Mackay, 1998) and wing size (directional selection; Gilchrist & Partridge, 2001) which is positively correlated with both thorax length and body weight (Reeve & Robertson, 1953;Sokoloff, 1966). While existing models accommodate variation in traits under both stabilizing and directional selection (Barton & Turelli, 1989;Kondrashov & Houle, 1994;Fry, Heinsohn & Mackay, 1998a;Barton & Keightley, 2002), we expect different genetic architecture to result from stabilizing rather than directional selection (Charlesworth & Hughes, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two traits in Drosophila known to be associated with fitness that are under different selection regimes are ovariole number (stabilizing selection; Wayne & Mackay, 1998) and wing size (directional selection; Gilchrist & Partridge, 2001) which is positively correlated with both thorax length and body weight (Reeve & Robertson, 1953;Sokoloff, 1966). While existing models accommodate variation in traits under both stabilizing and directional selection (Barton & Turelli, 1989;Kondrashov & Houle, 1994;Fry, Heinsohn & Mackay, 1998a;Barton & Keightley, 2002), we expect different genetic architecture to result from stabilizing rather than directional selection (Charlesworth & Hughes, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Selecting a body size-related trait for study depends both on considerations such as reproducibility, and the specific question being addressed. Allometric traits such as wing length and thorax length have the advantage over mass or volume of being conditionindependent: reproductive status (particularly in females) and starvation can influence estimators of body size such as mass (wet weight or dry weight) or volume, but do not affect determinate, allometric traits (Sokoloff, 1966). Thorax length is also associated with fitness, and is genetically correlated with female reproductive output (Partridge & Fowler, 1993;Nunney & Cheung, 1997), which could potentially involve ovariole number, as well as with male reproductive success (Partridge & Farquhar, 1983;Partridge et al, 1987;Reeve, Fowler & Partridge, 2000); both fecundity and male reproductive success are life-history traits that are most important early in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Wing size is a trait highly correlated with other measures of Drosophila body size (Robertson 1962;Sokoloff 1966;Cavicchi et al 1981); it can be measured with much greater accuracy than thorax length and it does not vary with age, nutrition, and reproductive status, as does body weight. For these reasons, wing area is frequently used as an index of body size.…”
mentioning
confidence: 99%
“…In Drosophila , larval development at low temperature reduces growth rate but increases final adult size (French et al, 1998). If we consider a direct relationship between body size and wing size to be common in Diptera (Briegel, 1990a; Briegel et al, 2001; Sokoloff, 1966), it could explain why larger wings were found in the colder regions of the Adamaoua highlands. Second, biotic processes affecting larvae are directly correlated to final adult size in Anopheles (Lyimo et al, 1992; Manoukis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, insect wings have been reported as an excellent model for studying morphological evolution in natural populations. Wing size is directly related to body size (Sokoloff, 1966) and there exists considerable evidence that size and shape are targets of natural selection (Soto et al, 2006). Moreover, they respond to environmental variation in complex ways, suggesting that the reaction norm may be part of an adaptive response (Carreira et al, 2006; Weber, 1990).…”
Section: Introductionmentioning
confidence: 99%